Rigid-tough balanced and high-conductivity glass fiber reinforced PP composite material and preparation method thereof

By adding carbon nanostructured materials CNS and superconducting carbon black to glass fiber reinforced polypropylene materials, the problem of improving the conductivity of existing materials and degrading mechanical properties is solved, and the rigid and tough balance and high conductivity are achieved, which is suitable for a variety of industrial fields.

CN119798861APending Publication Date: 2025-04-11SHANGHAI PRET COMPOSITES +3
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411962594.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

While the existing glass fiber reinforced polypropylene materials improve the conductivity, the mechanical properties of the existing glass fiber reinforced polypropylene materials have decreased, making it difficult to achieve both rigid and tough balance and high conductivity.

Method used

By adding new carbon nanostructured materials CNS, superconducting carbon black and suitable dispersion additives, the formulation system is optimized and the dispersion of conductive fillers in polypropylene resin is enhanced, thereby improving the conductive and mechanical properties of the material.

Benefits of technology

It has achieved the high conductivity of glass fiber reinforced PP composite materials and the high tensile strength, bending strength and bending modulus, and is suitable for the automotive industry, electronic appliances and electronic packaging fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005217550740000061
    Figure BDA0005217550740000061
  • Figure BDA0005217550740000071
    Figure BDA0005217550740000071
Patent Text Reader

Abstract

The invention discloses a rigid-tough balanced and high-conductivity glass fiber reinforced PP composite material and a preparation method thereof. The rigid-tough balanced high-conductivity glass fiber reinforced PP composite material is prepared from the following raw materials in percentage by weight: 40 to 90 percent of polypropylene resin (PP), 5 to 30 percent of chopped glass fiber, 0.1 to 10 percent of carbon nanostructure material CNS, 0.1 to 15 percent of superconductive carbon black, 0.1 to 10 percent of dispersing aid, 0.1 to 5 percent of compatilizer, 0.1 to 15 percent of flexibilizer, 0.1 to 5 percent of antioxidant and 0 to 2 percent of other aids. The rigid-tough balanced and high-conductivity glass fiber reinforced PP composite material disclosed by the invention has relatively high mechanical properties, excellent conductivity and excellent injection molding performance, and can be widely applied to the fields of automobile industry, electronic appliances and electronic packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a rigidity-toughness balanced, highly conductive glass fiber reinforced PP composite material and a preparation method thereof, which can be applied to the automotive industry, electronic appliances and electronic packaging fields, and belongs to the technical field of polymer material processing and modification. Background Art

[0002] Polypropylene (PP) has the advantages of good transparency, light weight, good heat resistance, low price, non-toxicity, good corrosion resistance, excellent electrical insulation, good processability, etc. It can be widely used in the automotive industry, electronic appliances, packaging, building materials, furniture, medical and other fields. However, polypropylene (PP) materials have large molding shrinkage and insufficient rigidity, which also limits the further expansion of its application range. While retaining most of the advantages of the raw materials, glass fiber reinforced polypropylene (PP) makes up for the shortcomings of the raw materials, such as large molding shrinkage and low rigidity, thus further expanding the application field of polypropylene materials.

[0003] With the development of society and the advancement of science and technology, many industrial fields have put forward antistatic and even high conductivity requirements for plastic materials. For example, high conductivity and wave-absorbing materials are needed near the radio frequency circuits, antennas and other components of vehicle-mounted millimeter-wave radars to effectively reduce the influence of radar clutter or antenna sidelobe signals, thereby improving the accuracy and reliability of radars. In addition, in the fields of electronic appliances, electronic packaging and industrial manufacturing, high strength, high heat resistance and high conductivity are also required for the plastic materials involved. Glass fiber reinforced polypropylene materials have also become a major research hotspot for the development of conductive materials due to their many advantages. The main way to give plastic materials conductive properties is to add various conductive fillers, such as conductive carbon black, graphite, carbon fiber, metal powder, metal fiber and carbon nanotubes. However, traditional conductive fillers have a high addition ratio, which will have an adverse effect on the original mechanical properties and processing properties of the material. Chinese patent CN112940393 A discloses a method for preparing a high-strength, antistatic glass fiber reinforced polypropylene material. By adding a high proportion of carbon nanotube powder, the glass fiber reinforced polypropylene material is given antistatic properties. The surface resistivity of the modified material can reach 10 6 , but the mechanical properties have decreased. Therefore, in order to obtain a high conductivity glass fiber reinforced PP composite material with a balance of rigidity and toughness, it is necessary to select a more efficient conductive filler and optimize the formulation system. Summary of the invention

[0004] The purpose of the present invention is to provide a glass fiber reinforced PP composite material with balanced rigidity and toughness and high conductivity and a preparation method thereof, so as to solve the deficiencies of the prior art.

[0005] The technical solution of the present invention is as follows:

[0006] A glass fiber reinforced PP composite material with balanced rigidity and toughness and high conductivity, prepared from the following raw materials by weight percentage:

[0007] Polypropylene resin (PP) 40-90%,

[0008] Chopped glass fiber 5-30%,

[0009] Carbon nanostructured material CNS 0.1~10%,

[0010] Superconducting carbon black 0.1~15%,

[0011] Dispersing aid 0.1~10%,

[0012] Compatibilizer 0.1~5%,

[0013] Toughening agent 0.1~15%,

[0014] Antioxidant 0.1~5%,

[0015] Other additives 0-2%.

[0016] The polypropylene resin (PP) is a mixture of homopolymer polypropylene and copolymer polypropylene. ℃ , under the test conditions of 2.16kg, the melt index is between 1 and 100g / 10min.

[0017] The chopped glass fibers have a length of 4.5 mm, a fiber diameter of 13 μm, a moisture content of ≤0.05%, and the surface of the glass fibers is modified by a silane-type active agent.

[0018] The carbon nanostructured material CNS is a multi-walled carbon nanotube material with a unique bifurcated structure and distributed in an array. Different from the traditional multi-walled carbon nanotube (CNT), it has a unique branch structure and better dispersibility.

[0019] The superconducting carbon black has a specific surface area greater than 200m 2 / g, oil absorption value (DBP) is less than 350ml / 100g.

[0020] The dispersing aid is one or more of polyethylene wax, silicone and polypropylene wax.

[0021] The compatibilizer is maleic anhydride grafted polypropylene (PP-g-MAH), and the grafting rate is 1.5%.

[0022] The toughening agent is ethylene / octene copolymer POE, at 190 ℃ Under the test conditions of 2.16 kg, the melt index is between 0.5 and 30 g / 10 min, and the density is between 0.86 and 0.92 g / cm 3between.

[0023] The antioxidant comprises a main antioxidant and an auxiliary antioxidant, wherein the main antioxidant is a hindered phenol or thioester antioxidant; and the auxiliary antioxidant is a phosphite or ester antioxidant.

[0024] The main antioxidant is one or more of 3,5-di-tert-butyl-4-hydroxybenzyl diethyl phosphate (3114), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (1010), and octadecyl thiodipropionate (DSTP); the auxiliary antioxidant is one or more of pentaerythritol distearyl diphosphite (618), tris(2,4-di-tert-butylphenyl) phosphite (168), and distearyl pentaerythritol diphosphite (619F).

[0025] The preparation method of the rigidity-toughness balanced, highly conductive glass fiber reinforced PP composite material comprises the following steps:

[0026] (1) Weigh polypropylene resin (PP), carbon nanostructured material CNS, superconducting carbon black, dispersing agent, compatibilizer, toughening agent, antioxidant and other additives according to the above proportions, and mix them in a high-speed mixer for 2 to 5 minutes.

[0027] (2) Weigh chopped glass fibers according to the above ratio.

[0028] (3) adding the uniform mixture in step (1) to the main feeder of the twin-screw extruder, and adding the corresponding chopped glass fibers in step (2) to the side feeder, and after the main feed material is melted, melt-blending and extruding granulation with the side feed material, the temperature of each section of the extruder is as follows: zone 1 90-100° C., zone 2 150-160° C., zone 3 225-235° C., zone 4 225-235° C., zone 5 225-235° C., zone 6 225-235° C., zone 7 220-230° C., zone 8 220-230° C., zone 9 220-230° C., zone 10 210-220° C., and the main engine speed is 500-600 rpm.

[0029] The present invention enhances the dispersibility of CNS and superconducting carbon black in reinforced PP resin by adding novel carbon nanostructured material CNS, superconducting carbon black and suitable dispersing aid, thereby giving glass fiber reinforced PP resin higher conductivity while further improving its tensile strength, flexural strength and flexural modulus. DETAILED DESCRIPTION

[0030] The present invention can be further described by the following preferred embodiments, but these embodiments are only for illustration and do not limit the scope of the present invention.

[0031] The main raw materials used in the examples and comparative examples of the present invention are as follows:

[0032] Copolymer polypropylene resin (PP): PP 8285E1, ExxonMobil;

[0033] Homopolymer polypropylene resin (PP): PPHP840N, CNOOC and Shell Petrochemical Co., Ltd.;

[0034] Chopped glass fiber: ECS305G, Chongqing International Composite Materials Co., Ltd.

[0035] Carbon Nanostructured Materials CNS: ATHLOS TM CNS, Cabot;

[0036] Superconducting carbon black: XCmax TM 22, Cabot;

[0037] Dispersing aid: PE wax, Clariant;

[0038] Compatibilizer: Maleic anhydride grafted polypropylene (PP-g-MAH), Huawen Chemical;

[0039] Toughening agent: POE-7467, Dow Chemical, USA;

[0040] Primary antioxidant: 1010, BASF, Germany;

[0041] Auxiliary antioxidant: 619F, SI Group;

[0042] Carbon black: m800, Cabot.

[0043] Example 1

[0044] 44.1 parts of copolymerized polypropylene resin PP 8285E1, 25 parts of homopolymerized polypropylene resin PPHP840N, 2 parts of carbon nanostructured material CNS, 1 part of dispersing aid PE wax, 2 parts of compatibilizer maleic anhydride grafted polypropylene, 5 parts of toughening agent POE-7467, 0.2 parts of primary antioxidant 1010, 0.2 parts of auxiliary antioxidant 619F and 0.5 parts of carbon black m800 were put into a high-speed mixer and mixed for 2 to 5 minutes. After being mixed evenly, the mixture was added to the main feeder of the twin-screw extruder; at the same time, 20 parts of short-cut glass fiber ECS305G were weighed and added to the side feeder. After the main feed material was melted, it was melt-blended and extruded and granulated with the side feed material to obtain a high-conductivity glass fiber reinforced PP composite material with balanced rigidity and toughness.

[0045] The temperatures of each section of the extruder are as follows: zone 1 90-100°C, zone 2 150-160°C, zone 3 225-235°C, zone 4 225-235°C, zone 5 225-235°C, zone 6 225-235°C, zone 7 220-230°C, zone 8 220-230°C, zone 9 220-230°C, zone 10 210-220°C, and the main engine speed is 500-600rpm.

[0046] Example 2

[0047] 43.1 parts of copolymerized polypropylene resin PP 8285E1, 25 parts of homopolymerized polypropylene resin PP HP840N, 3 parts of carbon nanostructured material CNS, 1 part of dispersing aid PE wax, 2 parts of compatibilizer maleic anhydride grafted polypropylene, 5 parts of toughening agent POE-7467, 0.2 parts of primary antioxidant 1010, 0.2 parts of auxiliary antioxidant 619F and 0.5 parts of carbon black m800 were put into a high-speed mixer and mixed for 2 to 5 minutes. After being mixed evenly, the mixture was added to the main feeder of the twin-screw extruder; at the same time, 20 parts of short-cut glass fiber ECS305G were weighed and added to the side feeder. After the main feed material was melted, it was melt-blended and extruded and granulated with the side feed material to obtain a high-conductivity glass fiber reinforced PP composite material with balanced rigidity and toughness.

[0048] The temperatures of each section of the extruder are as follows: zone 1 90-100°C, zone 2 150-160°C, zone 3 225-235°C, zone 4 225-235°C, zone 5 225-235°C, zone 6 225-235°C, zone 7 220-230°C, zone 8 220-230°C, zone 9 220-230°C, zone 10 210-220°C, and the main engine speed is 500-600rpm.

[0049] Example 3

[0050] 42.1 parts of copolymerized polypropylene resin PP 8285E1, 25 parts of homopolymerized polypropylene resin PP HP840N, 4 parts of carbon nanostructured material CNS, 1 part of dispersing aid PE wax, 2 parts of compatibilizer maleic anhydride grafted polypropylene, 5 parts of toughening agent POE-7467, 0.2 parts of primary antioxidant 1010, 0.2 parts of auxiliary antioxidant 619F and 0.5 parts of carbon black m800 were put into a high-speed mixer and mixed for 2 to 5 minutes. After being mixed evenly, the mixture was added to the main feeder of the twin-screw extruder; at the same time, 20 parts of short-cut glass fiber ECS305G were weighed and added to the side feeder. After the main feed material was melted, it was melt-blended and extruded and granulated with the side feed material to obtain a high-conductivity glass fiber reinforced PP composite material with balanced rigidity and toughness.

[0051] The temperatures of each section of the extruder are as follows: zone 1 90-100°C, zone 2 150-160°C, zone 3 225-235°C, zone 4 225-235°C, zone 5 225-235°C, zone 6 225-235°C, zone 7 220-230°C, zone 8 220-230°C, zone 9 220-230°C, zone 10 210-220°C, and the main engine speed is 500-600rpm.

[0052] Example 4

[0053] 41.1 parts of copolymerized polypropylene resin PP 8285E1, 25 parts of homopolymerized polypropylene resin PP HP840N, 3 parts of carbon nanostructured material CNS, 2 parts of superconducting carbon black XCmax TM 22, 1 part of dispersing agent PE wax, 2 parts of compatibilizer maleic anhydride grafted polypropylene, 5 parts of toughening agent POE-7467, 0.2 parts of primary antioxidant 1010, 0.2 parts of auxiliary antioxidant 619F and 0.5 parts of carbon black m800 are put into a high-speed mixer and mixed for 2-5 minutes. After being mixed evenly, the mixture is added to the main feeder of the twin-screw extruder; at the same time, 20 parts of short-cut glass fiber ECS305G are weighed and added to the side feeder. After the main feed material is melted, it is melt-blended with the side feed material, extruded and granulated, thereby obtaining a high-conductivity glass fiber reinforced PP composite material with balanced rigidity and toughness.

[0054] The temperatures of each section of the extruder are as follows: zone 1 90-100°C, zone 2 150-160°C, zone 3 225-235°C, zone 4 225-235°C, zone 5 225-235°C, zone 6 225-235°C, zone 7 220-230°C, zone 8 220-230°C, zone 9 220-230°C, zone 10 210-220°C, and the main engine speed is 500-600rpm.

[0055] Example 5

[0056] 40.1 parts of copolymerized polypropylene resin PP 8285E1, 25 parts of homopolymerized polypropylene resin PP HP840N, 3 parts of carbon nanostructured material CNS, 3 parts of superconducting carbon black XCmax TM 22, 1 part of dispersing agent PE wax, 2 parts of compatibilizer maleic anhydride grafted polypropylene, 5 parts of toughening agent POE-7467, 0.2 parts of primary antioxidant 1010, 0.2 parts of auxiliary antioxidant 619F and 0.5 parts of carbon black m800 are put into a high-speed mixer and mixed for 2-5 minutes. After being mixed evenly, the mixture is added to the main feeder of the twin-screw extruder; at the same time, 20 parts of short-cut glass fiber ECS305G are weighed and added to the side feeder. After the main feed material is melted, it is melt-blended with the side feed material, extruded and granulated, thereby obtaining a high-conductivity glass fiber reinforced PP composite material with balanced rigidity and toughness.

[0057] The temperatures of each section of the extruder are as follows: zone 1 90-100°C, zone 2 150-160°C, zone 3 225-235°C, zone 4 225-235°C, zone 5 225-235°C, zone 6 225-235°C, zone 7 220-230°C, zone 8 220-230°C, zone 9 220-230°C, zone 10 210-220°C, and the main engine speed is 500-600rpm.

[0058] Example 6

[0059] 33.1 parts of copolymerized polypropylene resin PP 8285E1, 25 parts of homopolymerized polypropylene resin PP HP840N, 3 parts of carbon nanostructured material CNS, 1 part of dispersing aid PE wax, 2 parts of compatibilizer maleic anhydride grafted polypropylene, 5 parts of toughening agent POE-7467, 0.2 parts of primary antioxidant 1010, 0.2 parts of auxiliary antioxidant 619F and 0.5 parts of carbon black m800 were put into a high-speed mixer and mixed for 2 to 5 minutes. After being mixed evenly, the mixture was added to the main feeder of the twin-screw extruder; at the same time, 30 parts of short-cut glass fiber ECS305G were weighed and added to the side feeder. After the main feed material was melted, it was melt-blended and extruded and granulated with the side feed material to obtain a high-conductivity glass fiber reinforced PP composite material with balanced rigidity and toughness.

[0060] The temperatures of each section of the extruder are as follows: zone 1 90-100°C, zone 2 150-160°C, zone 3 225-235°C, zone 4 225-235°C, zone 5 225-235°C, zone 6 225-235°C, zone 7 220-230°C, zone 8 220-230°C, zone 9 220-230°C, zone 10 210-220°C, and the main engine speed is 500-600rpm.

[0061] Comparative Example 1

[0062] 46.1 parts of copolymerized polypropylene resin PP 8285E1, 25 parts of homopolymerized polypropylene resin PP HP840N, 1 part of dispersing aid PE wax, 2 parts of compatibilizer maleic anhydride grafted polypropylene, 5 parts of toughening agent POE-7467, 0.2 parts of primary antioxidant 1010, 0.2 parts of auxiliary antioxidant 619F and 0.5 parts of carbon black m800 were put into a high-speed mixer and mixed for 2-5 minutes. After being mixed evenly, the mixture was added to the main feeder of the twin-screw extruder; at the same time, 20 parts of short-cut glass fiber ECS305G were weighed and added to the side feeder. After the main feed material was melted, it was melt-blended with the side feed material and extruded and granulated to obtain a glass fiber reinforced PP composite material.

[0063] The temperatures of each section of the extruder are as follows: zone 1 90-100°C, zone 2 150-160°C, zone 3 225-235°C, zone 4 225-235°C, zone 5 225-235°C, zone 6 225-235°C, zone 7 220-230°C, zone 8 220-230°C, zone 9 220-230°C, zone 10 210-220°C, and the main engine speed is 500-600rpm.

[0064] Comparative Example 2

[0065] 36.1 parts of copolymerized polypropylene resin PP 8285E1, 25 parts of homopolymerized polypropylene resin PP HP840N, 1 part of dispersing aid PE wax, 2 parts of compatibilizer maleic anhydride grafted polypropylene, 5 parts of toughening agent POE-7467, 0.2 parts of primary antioxidant 1010, 0.2 parts of auxiliary antioxidant 619F and 0.5 parts of carbon black m800 were put into a high-speed mixer and mixed for 2 to 5 minutes. After being mixed evenly, the mixture was added to the main feeder of the twin-screw extruder; at the same time, 30 parts of short-cut glass fiber ECS305G were weighed and added to the side feeder. After the main feed material was melted, it was melt-blended with the side feed material and extruded and granulated to obtain a glass fiber reinforced PP composite material.

[0066] The temperatures of each section of the extruder are as follows: zone 1 90-100°C, zone 2 150-160°C, zone 3 225-235°C, zone 4 225-235°C, zone 5 225-235°C, zone 6 225-235°C, zone 7 220-230°C, zone 8 220-230°C, zone 9 220-230°C, zone 10 210-220°C, and the main engine speed is 500-600rpm.

[0067] Performance evaluation and implementation standards:

[0068] In the above embodiments and comparative examples, the performance of the products was tested according to the following standards and conditions.

[0069] The apparent density is tested according to ISO 1183-1; the flexural strength and flexural modulus are tested according to ISO 178, the sample size is 80×10×4mm, the bending speed is 2mm / min, and the span is 64mm; the tensile strength is tested according to ISO527, the sample is type 1A, and the tensile speed is 5mm / min; the simply supported beam notched impact strength is tested according to ISO 179-1, the sample size is 80×10×4mm, the A-type notch is selected, and the test temperature is 23℃; the surface resistivity is tested according to ASTM D257.

[0070] The test results of various physical properties of the products obtained in Examples 1 to 6 and Comparative Examples 1 to 2 are listed in Table 1.

[0071] Comparing Examples 1 to 3 with Comparative Example 1 and Example 6 with Comparative Example 2, it can be seen that adding a small amount of carbon nanostructured material CNS can give the glass fiber reinforced PP material excellent electrical conductivity, and the surface resistivity of the reinforced PP material gradually decreases with the increase of CNS content, but when it reaches 10 3 Ω / sq. After the surface resistivity is reduced to 10 Ω / sq, it is difficult to further reduce it. At the same time, it is also found that adding carbon nanostructured material CNS can improve the tensile strength, flexural strength and flexural modulus of the reinforced PP material. The greater the amount of CNS added, the greater the improvement. At the same time, the notched impact strength remains basically unchanged. Comparing Example 2 with Example 4 and Example 5, it can be found that the composite use of superconducting carbon black and carbon nanostructured material CNS can further reduce the surface resistivity of the reinforced PP material, which can reach 10 2 Ω / sq, indicating that the electrical conductivity of the enhanced PP material is further improved. At the same time, it is also found that the tensile strength, flexural strength and flexural modulus of the enhanced PP material are further improved after a small amount of superconducting carbon black and carbon nanostructured material CNS are compounded.

[0072] The present invention obtains a glass fiber reinforced PP composite material with balanced rigidity and toughness and high conductivity. The material not only has excellent conductive properties, but also has improved tensile strength, flexural strength and flexural modulus to a certain extent compared with conventional glass fiber reinforced PP materials. The material can be used in the automotive industry, electronic appliances, electronic packaging and other fields.

[0073] Table 1 Physical properties test results of products obtained in Examples and Comparative Examples

[0074]

[0075]

[0076] The above embodiments are for better illustrating the specific contents of the present invention, but the protection scope of the present invention is not limited thereto. Any researcher familiar with the technical field can easily change or replace these embodiments, and apply the basic principles of the present invention to other embodiments without creative work. Therefore, the protection scope of the present invention should be based on the protection scope defined by the claims.

Claims

1. A glass fiber reinforced PP composite material with balanced rigidity and toughness and high conductivity, characterized by: The raw materials are prepared according to the following weight percentages: Polypropylene resin 40~90%, Chopped glass fiber 5-30%, Carbon nanostructured material CNS 0.1~10%, Superconducting carbon black 0.1~15%, Dispersing aid 0.1~10%, Compatibilizer 0.1~5%, Toughening agent 0.1~15%, Antioxidant 0.1~5%, Other additives 0-2%.

2. The glass fiber reinforced PP composite material with balanced rigidity and toughness and high conductivity according to claim 1, characterized in that: The polypropylene resin is a mixture of homopolymer polypropylene and copolymer polypropylene, and has a melting index of 1 to 100 g / 10 min under the test conditions of 230° C. and 2.16 kg.

3. The glass fiber reinforced PP composite material with balanced rigidity and toughness and high conductivity according to claim 1, characterized in that: The chopped glass fibers have a length of 4.5 mm, a fiber diameter of 13 μm, a moisture content of ≤0.05%, and the surface of the glass fibers is modified by a silane-type active agent.

4. The glass fiber reinforced PP composite material with balanced rigidity and toughness and high conductivity according to claim 1, characterized in that: The carbon nanostructured material CNS is a multi-walled carbon nanotube material distributed in an array and having a unique bifurcated structure.

5. The glass fiber reinforced PP composite material with balanced rigidity and toughness and high conductivity according to claim 1, characterized in that: The superconducting carbon black has a specific surface area greater than 200m 2 / g, oil absorption value (DBP) is less than 350ml / 100g.

6. The rigidity-toughness balanced, highly conductive glass fiber reinforced PP composite material according to claim 1, characterized in that: The dispersing aid is one or more of polyethylene wax, silicone and polypropylene wax.

7. The glass fiber reinforced PP composite material with balanced rigidity and toughness and high conductivity according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted polypropylene (PP-g-MAH), and the grafting rate is 1.5%.

8. The rigidity-toughness balanced, highly conductive glass fiber reinforced PP composite material according to claim 1, characterized in that: The toughening agent is ethylene / octene copolymer POE, and under the test conditions of 190° C. and 2.16 kg, the melt index is between 0.5 and 30 g / 10 min, and the density is between 0.86 and 0.92 g / cm3.

9. The glass fiber reinforced PP composite material with balanced rigidity and toughness and high conductivity according to claim 1, characterized in that: The antioxidant comprises a main antioxidant and an auxiliary antioxidant, wherein the main antioxidant is a hindered phenol or thioester antioxidant; and the auxiliary antioxidant is a phosphite or ester antioxidant.

10. The glass fiber reinforced PP composite material with balanced rigidity and toughness and high conductivity according to claim 9, characterized in that: The main antioxidant is one or more of 3,5-di-tert-butyl-4-hydroxybenzyl diethyl phosphate (3114), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (1010), and octadecyl thiodipropionate (DSTP); the auxiliary antioxidant is one or more of pentaerythritol distearyl diphosphite (618), tris(2,4-di-tert-butylphenyl) phosphite (168), and distearyl pentaerythritol diphosphite (619F).

11. A method for preparing a rigidity-toughness balanced, highly conductive glass fiber reinforced PP composite material according to any one of claims 1 to 10, characterized in that: The steps are as follows: (1) Weigh polypropylene resin (PP), carbon nanostructured material CNS, superconducting carbon black, dispersing aid, compatibilizer, toughening agent, antioxidant and other additives according to the ratio described in claim 1, and mix them in a high-speed mixer for 2 to 5 minutes; (2) weighing chopped glass fibers according to the ratio described in claim 1; (3) adding the uniform mixture in step (1) to the main feeder of the twin-screw extruder, and adding the corresponding chopped glass fibers in step (2) to the side feeder, and after the main feed material is melted, melt-blending and extruding granulation with the side feed material, the temperature of each section of the extruder is as follows: zone 1 90-100° C., zone 2 150-160° C., zone 3 225-235° C., zone 4 225-235° C., zone 5 225-235° C., zone 6 225-235° C., zone 7 220-230° C., zone 8 220-230° C., zone 9 220-230° C., zone 10 210-220° C., and the main engine speed is 500-600 rpm.

Citation Information

Patent Citations

  • Carbon nanotube master batch and preparation method and application thereof

    CN112175300A

  • Preparation method of high-strength antistatic glass fiber reinforced polypropylene material

    CN112940393A

  • Intelligent pressure sensing elastomer foaming material

    CN114350055A

  • High-strength, high-modulus and high-conductivity shielding material and preparation method thereof

    CN117924916A

  • Fiber-reinforced modified flame-retardant antistatic PP composition and preparation method thereof

    CN118421010A